BERMAIN SAMBIL BELAJAR: LAGU SEBAGAI KUNCI PENGUASAAN BAHASA INGGRIS ANAK SD - Magvirah Octasary; Indry Widyasti Anwar; Anitha Thalib Mbau (PT. CASA CENDEKIA MEDIA, 2024)
Mastering English from an early age has many benefits, especially if taught in elementary school. By mastering English, children will have greater opportunities in the future. This service aims to improve the English proficiency of elementary school children in Sausu Taliabo Village from the age of 7 to 10 years through the Family Members song. Songs have great potential in language learning. Through songs, the learning atmosphere will be more fun and make children more motivated to actively participate in learning. Using songs can improve children's memory, understand vocabulary, help to develop pronouncation skills with clear intonation and also provide a meaningful and unforgettable learning experience. This activity goes through several stages, namely preparation, teaching, and evaluation. The application of songs in English learning has proven to be successful in creating a creative and innovative learning experience for children who live in Sausu Talibo Village, Parigi Moutong District, Central Sulawesi.